Penggunaan handout bermuatan kecerdasan komprehensif pada model generative learning dalam pembelajaran hukum newton siswa kelas X di SMAN 5 Padang - Firna Yolanda; akmam akmam; silvi yulia sari (Universitas Negeri Padang, 2020)
Student’s compalincy in physic’s material on the senior hight school is not One factor that causes low student competency is the low understanding of students in understanding physics learning material. One solution that will support the achievement of all student physics competencies both from knowledge competencies, religious attitudes, social attitudes, and skills is the use of handouts. The handout designed in this study aims to investigate the effect of using handouts on Newton's legal material with a comprehensive intelligence on the generative learning model on the competency achievement of class X students at SMAN 5 Padang. Type of research is a quasi experimental research with Randomized Control Group Only Design. The research population was all students of grade X students of SMAN 5 Padang who were enrolled in the Academic Year 2017/2018. Sampling technigue was pourposive sampling with class X MIA 3 as the experimental class and class X MIA 4 as the control class. The research instruments were in the form of learning outcomes tests for knowledge competencies, attitude observation sheets and skills competency performance assessment sheets. The data analysis technique uses comparism mean test, a simple linear regression test, and a correlation test at the 0.05 significance level for knowledge competence, while for competency attitudes and skills using graphics.